Hall Effect and transient surface photovoltage (SPV) study of Cu3BiS3 thin films - F. Mesa; A. Dussan; B. A. Paez-Sierra; H. Rodriguez-Hernandez (Universitas Scientiarum)
Here, we present the electrical properties of the compound Cu3BiS3 deposited by co-evaporation. This new compound may have the properties necessary to be used as an absorbent layer in solar cells. The samples were characterized by Hall effect and transient surface photovoltage (SPV) measurements. Using Hall effect measurements, we found that the concentration of n charge carriers is in the order of 1016 cm-3 irrespective of the Cu/Bi mass ratio. We also found that the mobility of this compound (μ in the order of 4 cm2 V-1s-1) varies according to the transport mechanisms that govern it and are dependent on temperature. Based on the SPV, we found a high density of surface defects, which can be passivated by superimposing a buffer layer over the Cu3BiS3 compound.